The Reality of the administrative Supervision of the Ministry of Youth and Sports Directorates and its Role In Improving the Administrative Level of Its Directorates - Hantosh, Salam; Saad, Samir; Flaih, Sahraa (Journal of Physical Education, 2018)
The Reality of the administrative Supervision of the Ministry of Youth and Sports Directorates and its Role In Improving the Administrative Level of Its Directorates In this study, the researchers sought to identify the reality of the administrative supervision of the Ministry of Youth and Sports directorates and the role it plays in improving the administrative level and what are the means and tools that are followed and used by the supervisors to improve its work from the point of view of its members, which amounted (984). The researchers used the descriptive method. The study was conducted in the period from 3/9/2018 to 1/21/2018. The administrative supervision and administrative improvement scales were used on the sample on 11/10/2018 on the sample of the research. The number of valid questionnaires was (309) and the five - variable scale was corrected. The field of (tools and means of supervision) has reached the highest degree within the axes as it reached its arithmetic mean (2.32) The field (organizational structure) has took (2.10) The field of (requirements for the effectiveness of supervision) has reached (2.00) While the measure of administrative improvement was seven statements. The researchers concluded that the field of tools and means of supervision was highly responsive while the organizational structure was the average response, and it was found that there is a large contribution to the speed of error detection and the accuracy of information to improve administrative performance.